Impact of earthquake-induced building debris on urban network functionality and citizen accessibility to urban functions - Koren, David; Rus, Katarina (Frontiers in Built Environment, 2025)
Cities operate as complex socio-spatial systems, composed of interconnected networks formed by diverse physical and social components. Dynamic interactions among these components sustain the city’s functionality, support the fulfilment of fundamental human needs, and ultimately determine the quality of life for urban residents. Urban resilience to earthquakes is traditionally assessed through physical damage analyses, yet such evaluations often overlook human-centred impacts on the quality of life. This study introduces a novel framework for evaluating the accessibility of citizens to essential urban functions post-earthquake, with these functions assessed through access to the corresponding facilities, and emphasising human needs rather than mere structural vulnerability. The proposed approach integrates seismic fragility assessments with graph theory-based accessibility metrics, capturing how damage to buildings and road blockages caused by earthquake-induced building debris affect the ability of residents to access vital urban functions. By integrating a panel of experts, the research examines the shifts in the hierarchy of human needs following seismic events. The proposed model is tested on a case study of a small Mid-European town under different seismic scenarios and evaluation approaches. The analysis shows that strong earthquakes can result in severe fragmentation of the urban network, with up to one-third of the population losing access to essential services. Educational and work-related functions emerge as particularly vulnerable, while healthcare accessibility proves more stable due to spatial distribution and facility robustness. Findings reveal a critical distinction between structural and functional vulnerability. A city may preserve most of its physical structures but still suffer major functional collapse if key services become inaccessible. This distinction underscores the need for spatial strategies that ensure the redundancy and dispersion of critical urban functions, particularly in historically dense or infrastructure-dependent areas. Building upon these findings, this study offers a methodology for assessing urban resilience by prioritising accessibility and human needs, aiding planners in improving emergency preparedness and long-term recovery.